On the Notion of Equilibrium and Disequilibrium - Frisch, Ragnar (Review of Economic Studies, 1936)
On the Notion of Equilibrium and Disequilibrium Get access Ragnar Frisch Ragnar Frisch Oslo Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 3, Issue 2, February 1936, Pages 100–105, https://doi.org/10.2307/2967500 Published: 01 February 1936